Abnormal NFAT5 Physiology in Duchenne Muscular Dystrophy Fibroblasts as a Putative Explanation for the Permanent Fibrosis Formation in Duchenne Muscular Dystrophy - Herbelet, Sandrine (Int J Mol Sci, 2020)
Duchenne muscular dystrophy (DMD) is characterized by chronic inflammation and fibrotic tissue production by fibroblasts. The promyogenic factor nuclear factor of activated T-cells 5 (NFAT5) is virtually present in all cells, responding to hyperosmolar or pro-inflammatory stress. In embryogenic fibroblasts, absence of NFAT5 results in cell cycle arrest. Here, unaffected skeletal muscle fibroblasts from one healthy donor showed NFAT5 nuclear translocation upon hyperosmolar stress and normal cell viability. Absence of NFAT5 translocation under pro-inflammatory conditions resulted in decreased cell growth (Incucyte ZOOM). In DMD skeletal muscle fibroblasts from one DMD patient, NFAT5 was merely located in the nucleus. Exposure to hyperosmolar conditions or pro-inflammatory cytokines IFN-γ, IL-1β and TNF-α had no influence on NFAT5 physiology (immunofluorescence, western blotting, RT-qPCR). Hyperosmolarity resulted in decreased cell viability and pro-inflammatory stress in unaltered cell growth. These findings suggest that NFAT5 is vital to DMD fibroblast survival. Exposure to pro-inflammatory or hyperosmolar stress in DMD fibroblasts results in an unexpected NFAT5 response, where fibroblasts are not triggered by inflammatory cytokines and do not withstand hyperosmolarity. Chronic inflammation could be viewed as a non-restrictive factor in the formation of fibrosis in DMD. Abnormal NFAT5 physiology could provide a molecular explanation for permanent fibrotic matrix production by DMD fibroblasts.